Association Between 5-Alpha Reductase Inhibitor Use and The Risk of Depression: A Meta-Analysis - Deng, Tuo; Duan, Xiaolu; He, Zihao; Zhao, Zhijian; Zeng, Guohua (Urology Journal, 2020)
Purpose: To explore the association between 5α-reductase inhibitors (5ARIs) use and risk of depression based on published literature through a meta-analysis. Materials and methods: A comprehensive literature search was conducted by searching Pubmed, Embase, Cochrane Library, CBM, CNKI, and VIP databases up to June, 2019. Summarized risk ratios (RRs) with 95% confidence intervals (CIs) were calculated to evaluate the strength of association between 5ARIs and depression. Subgroup analyses were performed according to population, 5ARI types, degree of depression, and publication date. Registered in PROSPERO under number CRD42018096147. Results: A total of 6 clinical studies with 265672 participants were included in our meta-analysis. The application of 5ARIs could significantly increase the risk of depression based on both pooled unadjusted (95% CI: 1.28-2.78, RR = 1.89, P = .001) and multivariable adjusted RRs (95% CI: 1.01-1.17, RR = 1.09, P = .03). In subgroup analyses, dutasteride was associated with depression significantly (95% CI: 1.37-1.70, RR = 1.53, P < .001), while finasteride was not. As to the degree of depression, 5ARIs mainly caused mild depression (95% CI: 1.91-2.33, RR = 2.11, P < .001), instead of moderate or severe depression. Conclusion: We concluded that 5ARIs could potentially increase the risk of depression. Clinicians need to carefully consider the use of 5ARIs for benign prostatic hyperplasia and androgenic alopecia patients, especially those exhibiting risk factors for depression or those who have a previous history of depression. More studies with larger sample size and comprehensive study design are needed to further verify our outcomes.